Calculation of the velocities induced by the trailing vorticity in the rotor plane of a horizontal-axis turbine or propeller - Wood, David H. (Frontiers in Energy Research, 2024)
Lifting line (LL) analysis of propellers and horizontal-axis turbines requires the axial and circumferential velocities induced by the vortex system representing the blades and the trailing vorticity. If the blades are straight and radial, the induced velocities along the LLs are due only to the trailing vorticity. Accurate two-term approximations for these velocities have been developed from the exact Kawada–Hardin (KH) equations for the velocity field of a doubly infinite helical vortex of constant pitch and radius, Wood et al. (Ocean Engineering, 2021, 235). This paper describes a straightforward extension of the approximations to give the induced velocities anywhere in the equivalent of the rotor plane for a doubly infinite helix. The third term in the approximation of the KH equations is derived and compared to an alternative third term due to Okulov (Journal of Fluid Mechanics, 2004, 521, 319–342). Both three-term approximations produce a small improvement in accuracy over the two-term approximations for a range of operating conditions for turbines and propellers. Okulov’s third term is superior. To determine the induced velocities for a singly infinite trailing vortex behind a rotor, an additional equation is derived from the Biot–Savart law. Numerical examples show that the resulting equations provide accurate estimates for the induced velocities over the rotor plane. The main application of the analysis is to account for blade sweep and coning by including the angle between the vortex origin and the control point at which the velocities are required, often the center of each blade element.